2019
DOI: 10.1159/000500467
|View full text |Cite
|
Sign up to set email alerts
|

Is There any Association between Urothelial Carcinoma of the Bladder and Human Papillomavirus? A Case-Control Study

Abstract: <b><i>Objectives:</i></b> Human papillomavirus (HPV) is a well-known oncogenic virus associated with anogenital carcinomas. Despite the anatomical proximity of the bladder and the anogenital region, the relationship between HPV and urothelial carcinoma of the bladder (UCB) is still a controversial issue. This study aimed to test the urethral swabs and first-void urine samples of patients with UCB for HPV-Deoxyribonucleic acid (DNA) using polymerase chain reaction (PCR) assay and to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 0 publications
1
34
0
Order By: Relevance
“…The results of a previous study suggested an association between the high-risk types of HPV and low-grade bladder cancer [6]. However, a recent study that used fresh tissue samples for detecting HPV refuted a relationship between this virus and bladder tumor grade [27].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The results of a previous study suggested an association between the high-risk types of HPV and low-grade bladder cancer [6]. However, a recent study that used fresh tissue samples for detecting HPV refuted a relationship between this virus and bladder tumor grade [27].…”
Section: Discussionmentioning
confidence: 96%
“…Quality of PCR might be slightly higher in FFT samples compared to FFPE; however, the difference is trivial and non-significant in many cases [35,36]. For instance a previous study declared the superiority of fresh tissue samples over FFPE [27]. However, difficulties in acquiring and maintaining FFT samples results in much more common use of FFPE [37].…”
Section: Discussionmentioning
confidence: 99%
“…It is implicated in about 90% of anogenital cancers 7 . Although several case–control studies suggested the potential involvement of HPV in UC, 8‐10 the causality of HPV in UC was not established. Previous studies reported contrasting HPV detection rates of 0%–81% in UC 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…1 Unlike most other viruses, the classification of HPVs is based on their genomic sequence homology instead of their antigenic structure. 2 In recent years, hundreds of different HPV types have been found. According to the malignant progression of the disease, HPV is mainly divided into high-risk and low-risk types.…”
Section: Introductionmentioning
confidence: 99%
“…1,3 The high-risk types, such as HPV-16, 18, 52, and 58, are closely associated with cervical cancer. 2,4 HPV imposes a substantial socioeconomic burden mainly due to its oncogenic potential. 5 HPV-16 and HPV-18 are found to be the most common HPV infection types in the world.…”
Section: Introductionmentioning
confidence: 99%